ChemInform Abstract: Foxo3a Inhibitors of Microbial Origin, JBIR‐141 and JBIR‐142. Issue 13 (March 2016) - Kawahara, Teppei; Kagaya, Noritaka; Masuda, Yuichi; Doi, Takayuki; Izumikawa, Miho; Ohta, Kumiko; Hirao, Atsushi; Shin‐ya, Kazuo
Abstract: Title compounds (I) and (II) are isolated from soil‐derived Streptomyces sp.